Standardization and organoleptic evaluation of agathi (Sesbania grandiflora) leaves incorporated traditional weaning recipes - Jhansi, Sana; G, Gayathri; A J, Hemamamalini (Journal of Postharvest Technology, 2021)
For every individual, nutrition is very important to prevent the nutrient deficiencies and to help good growth of infants. To make the  availability of nutrient rich food even in lower income families the present study was undertaken to formulate nutrient dense complementary  foods for infants with the use of locally available green leafy vegetable which is rich in calcium and iron. In present study fresh agathi  leaves was taken cleaned, shade dried and pulverized. Incorporating the agathi leaves powder, 3 different variations of rajma kitchidi,  urad dhal kitchidi and sathumavu kanji was made V1(5 gm agathi leaves powder), V2(10 gm agathi leaves powder), V3 (15 gm agathi  leaves powder). Sensory quality evaluation was done using 9 point hedonic rating score by a panel of 10 judges. From 3 variations of all  3 recipes the variation - I recorded the highest hedonic value. Acclerated shelf life analysis found product to be microiologically safe for  48 hours in room temperature and 72 hours safe at refrigerated temperature respectively. The study concluded addition of agathi leaves  into standard recipe increased the nutrient composition especially calcium and iron content and can also recommended for adult and  elderly people to meet their requirements.
Keywords: Sesbania grandiflora; Agathi; 9 point hedonic rating scale; sensory analysis; shelf life